2019
DOI: 10.1007/s10826-019-01450-4
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning and Not Family Structure Predicts Adolescents’ Reasoning and Math Skills

Abstract: Objectives A large body of research exists on families and their impact on children's developmental outcomes. Fewer studies examine family processes within different family structures and their impact on adolescents. This study extends prior work by evaluating associations between family structure (two biological parents, single-parent-mother only, and blended families with a step parent), family functioning (communication, cohesion and flexibility) and adolescents' logic and reasoning skills and math performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…In fact, research has found that parents in nuclear families devote more time to their children than parents in single-parent and reconstituted families (Fallesen & Gähler, 2020) and that parental separation is associated with lower levels of parental sensitivity and emotional warmth/support, higher reactivity, and increased use of punishment (Friesen et al, 2017). Thus, family functioning seems to be more important than the family structure in predicting a child's social and emotional behavior (Lin et al, 2019;Simões et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, research has found that parents in nuclear families devote more time to their children than parents in single-parent and reconstituted families (Fallesen & Gähler, 2020) and that parental separation is associated with lower levels of parental sensitivity and emotional warmth/support, higher reactivity, and increased use of punishment (Friesen et al, 2017). Thus, family functioning seems to be more important than the family structure in predicting a child's social and emotional behavior (Lin et al, 2019;Simões et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the survey lacks information on the exact timing of changes in household membership. In addition to family structure, future research should examine family functioning, which has been found to be a stronger predictor of math skills than family structure ( Lin et al 2019 ). However, this current line of research can be further developed to consider grandparents, a conderation that was not a component of the family functioning analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the concept of family functioning has gained some notoriety. However, most study outcomes focus on well-being as opposed to academic outcomes (Lin et al, 2019). In this study, students with family difficulties were 85% more likely than those without to experience SD.…”
Section: Discussionmentioning
confidence: 99%